The Antibiotic Resistance Crisis - Kumar Jha, Keshav; Saini, Subham; Raj, Aman; ., Shreyasi; Bishnoi, Hansraj (Asian Journal of Pharmaceutical Research and Development, 2023)
Numerous deaths from infectious diseases have raised public awareness of their dangers, promoting global antimicrobial research. However, antibiotic demand and use, on the other hand, have increased antibiotic levels in natural ecosystems. Natural selection and adaptation induced antibiotic resistance gene mutations in bacterial populations. Dissemination of antibiotic resistance genes in ecosystems resulted in the emergence of antibiotic-resistant bacteria, leading to a variety of antibiotic-resistant diseases on a global scale. This review paper provides an overview of the antibiotic discovery history, antibiotic screening techniques, and industrial antibiotic production processes. In addition, the emergence of antibiotic-resistant microorganisms and the antibiotics’ impact on the environment have been reviewed, and suggestions were given. The ecological perspective on antibiotic resistance has also been discussed. New drug development seems to be the prime requisite now to control microbes that no longer respond to the drug.